THE USE OF PROCESS IN JUZ AMMA OF HOLY QURAN - Ulfian Haitami; Meisuri Meisuri (State University of Medan, 2012)
Abstract One aim of this article is to show through a concrete example how speech function and speech role used in Holy Quran. The texts were taken from the verses in Juz Amma of Holy Quran. All surahs in Juz Amma of Holy Quran were taken as the data by using dexcriptive qualitative method. The result shows that the six types of process are found in the verses in Juz Amma of Holy Quran. Material Process is dominantly used because many surahs in Juz Amma of Holy Quran contain about action, activity, things that are doing or happened physically, bodily, and materially. Keywords: Juz Amma of Holy Quran, process, transitivity